Factors Associated With Early Readmission Among Patients Discharged to Post‐Acute Care Facilities. Issue 6 (3rd March 2017) - Horney, Carolyn; Capp, Roberta; Boxer, Rebecca; Burke, Robert E.
Abstract : Background: Over a quarter of Medicare patients admitted to the hospital are discharged to post‐acute care (PAC) facilities, but face high rates of readmission. Timing of readmission may be an important factor in identifying both risk for and preventability of future readmissions. This study aims to define factors associated with readmission within the first week of discharge to PAC facilities following hospitalization. Design and Measurements: This was a secondary analysis of the 2011 Healthcare Cost and Utilization Project (HCUP) State Inpatient Databases (SID) for California, Massachusetts, and Florida. The primary outcome was all‐cause readmission within 7 days after hospital discharge, compared to readmission on days 8–30, for patients aged 65 and older who were discharged from the hospital to a PAC facility. Predictor variables included patient, index hospitalization, and hospital characteristics; multivariable logistic regression was used to identify significant predictors of readmission within 7 days. Results: There were 81, 173 hospital readmissions from PAC facilities in the first 30 days after hospital discharge. Patients readmitted within the first week were older, white, urban, had fewer comorbid illnesses, had a higher number of previous hospital admissions, and less commonly had Medicare as a payer. Longer index hospital length of stay (LOS) was associated with decreased risk of early readmission (OR 0.74; 95% CI 0.70–0.74 for LOS 4–7 days and 0.60; 95% CI 0.56–0.64 for LOS ≥8 days). Conclusions: Shorter length of index hospital stay is associated with earlier readmission and suggests that for this comorbid, older population, a shorter hospital stay may be detrimental. Readmission after 1 week is associated with increased chronic disease burden, suggesting they may be associated with factors that are less modifiable.